The Changes of Premenstrual Symptoms after Aerobic Exercise Intervention - Noor, Sirajudin; Norfitri, Raihana (Jurnal NERS, 2015)
Introduction: Premenstrual syndrome (PMS) is a group of physical symptoms, emotions and behaviors that occur cyclically during the luteal phase of the menstrual cycle and disappear after menstruation happened. Those symptoms might cause suffering for women and thus require treatment. Aerobic physical activity can raise the level of endorphins, decrease estrogen, increase oxygen transport in muscle and improve psychological well-being. The purpose of this study is to identify the differences in the effect of aerobic exercise and health education on the symptoms of premenstrual syndrome. Method: This study used quasy ekspriment with pre-posttest control group design. The research was conducted by comparing the symptoms of PMS complaints before and after treatment in the control group (education health) and the experimental group (aerobics).The research performed at the Academy of Nursing Intan Martapura and Midwifery Academy Banjarbaru with all students who registered as a student of the Academy of Nursing Intan Martapura and Midwifery Academy Banjarbaru as the subjects. The technique sampling used in this study was purposive sampling The number of sample was 40 respondents. Result: Based on pearson correlation test in cases and controls prior to treatment showed Î± > 0.05 (0.862), meant there was no correlation PMS between cases and controls. After treatment in cases and controls showed Î± <0.05 (0.018), mean there was a correlation between gymnastics aerobics with PMS complaints andPMS symptoms complaints, with the weak level of strength 0,373. From the comparative t-test in cases and controls prior to treatment showed signs â¥ 0.05 (0.862), means there was no difference of PMS complaints in cases and control group. After the treatment in cases and controls showed signs of < 0.05 (0.018), which means there was differences in symptoms of premenstrual complaints on cases that do aerobics with controls who received health education. From Paired t-test on cases before and after treatment in the form of aerobics showed sign result 0.000 < 0.05, which means that there were differences in symptoms of premenstrual complaints and menstrual complaints before and after aerobics exercise. In control group before and after treatment showed a sign of health education 0.056 â¥ 0.05 meant no differences on PMS complaints and PMS symptoms complaints between before and after the education. Analysis and Discusssion: For the students who had health complaints of PMS symptoms, it is suggested to perform regular aerobic exercise as one way to reduce the symptoms of PMS complaints.Keywords: PMS symptoms complaints, aerobics, health education